Assessment of allergen tolerance breakdown levels in local and classical allergic rhinitis - A. V. Klimov; Z. V. Salakhutdinova; O. A. Naidina; V. V. Klimov; V. S. Sviridova; N. A. Pronina; M. I. Slezkin (Медицинская иммунология, 2022)
Local allergic rhinitis, a new endotype of allergic rhinitis discerned by researchers of the Spanish Allergy School, is now in the focus of interest of international allergological community. A special feature of local allergic rhinitis, which, being similar to conventional signs of allergic rhinitis, is, however, characterized by absence of systemic atopy manifestations, e.g., an increased total serum IgE content and positive allergic skin tests. In order to assess the level of tolerance breakdown to allergens in local and classical allergic rhinitis, we have studyed concentrations of IL-4, IL-22, and IFNγ in three biological fluids, blood, nasal secretions, and skin exudate. The whole study cohort consisted of 82 patients aged 18 to 60 years with established allergic rhinitis. The diagnosis was based on counseling by allergologist/immunologist, including clinical case history and possible inheritance of atopy as well as videorhinoscopy performed by an ENT specialist. The procedure of videorhinoscopy allowed to specify allergic origin of rhinitis and exclude the patients with non-allergic forms of the disease, but it did not enable us to differentiate between the endotypes of classic and local allergic rhinitis. Subsequently, all patients have been divided into two subgroups based on the criteria of systemic atopy: (1) with a high content of serum total IgE and positive skin allergy tests (n = 41) and (2) with a significantly lower concentration of IgE and negative allergy tests (n = 41). It was concluded that the patients with classic allergic rhinitis prevailed in the 1st subgroup, whereas local rhinitis predominated in the 2nd group. The study of IL-4, IL-22 and IFNγ concentrations in the three biological fluids allowed us to presume that the 1st subgroup was characterized by increased content of IL-4 and IL-22 in blood and skin exudate in comparison with controls, and the 2nd subgroup showed a decrease in IFNγ to control values. The cytokine concentrations in nasal secretions were not representative for the subgroups studied. The result has been interpreted as the absence of tolerance breakdown to causal allergens in the patients with local allergic rhinitis at the systemic level. The obtained data could be used in development of a diagnostic biomarker system for this specific endotype of allergic rhinitis, thus avoiding potential diagnostic errors which occurred in the past, when this endotype was classified as non-allergic form of the disease, thus administering non-adequate treatment, e.g., allergen-specific immunotherapy, which could be prescribed in these cases.